Prognostic factors and treatment outcomes in EGFR-mutated NSCLC with malignant pleural effusion: focus on intrathoracic chemotherapy and EGFR-TKI therapy - Huang, Zhuohao; Li, Jinmei; Ye, Haiyin; Huang, Zhong; Wang, Yongcun; Xie, Yuliu; Huang, Xiaobi; Cheng, Zhen; Chen, Yuting; Xiao, Chang; Li, Mingchun; Su, Wenmei (Frontiers in Oncology, 2025)
ObjectiveIn treatment-naïve patients with EGFR-mutated non-small-cell lung cancer (NSCLC) complicated by malignant pleural effusion (MPE), we first investigated whether the addition of intrathoracic chemotherapy (ICT) to first-line EGFR tyrosine-kinase inhibitors (EGFR-TKIs) confers superior therapeutic efficacy or survival outcomes compared with EGFR-TKI monotherapy. Subsequently, multivariable analyses were performed to identify independent prognostic determinants across the entire cohort, thereby informing individualized treatment selection.MethodsA retrospective analysis was performed, ultimately including 169 individuals diagnosed with stage IVA-IVB NSCLC who tested positive for EGFR mutations and exhibited malignant pleural effusion at initial presentation. All patients underwent either first-line EGFR-TKI monotherapy or a combination of intrathoracic chemotherapy with EGFR-TKIs. Patients were grouped according to receipt of EGFR-TKIs with or without concomitant ICT and by pertinent clinical characteristics. Kaplan-Meier survival analysis and Cox proportional hazards regression models were utilized to evaluate survival outcomes and potential influencing factors. The study’s objective was to determine the differential impact of intrathoracic chemotherapy plus EGFR-TKIs versus EGFR-TKIs alone on therapeutic efficacy and survival, while concurrently elucidating the independent prognostic relevance of clinical characteristics in EGFR-mutated NSCLC patients presenting with malignant pleural effusion, thereby guiding treatment prioritization.ResultsAmong patients with stage IVA-IVB NSCLC who were EGFR mutation-positive and presented with malignant pleural effusion at initial diagnosis, a comparative analysis showed no statistically significant differences in median progression-free survival (mPFS) (18.2 months vs. 15.0 months, Log Rank p = 0.07) and median overall survival (mOS) (29.2 months vs. 30.6 months, Log Rank p = 0.09) between EGFR-TKI monotherapy and the combination of thoracic perfusion chemotherapy with EGFR-TKIs. Further univariate and multivariate analyses indicated that the combination of EGFR-TKIs and ICT did not significantly impact PFS or OS. However, the use of third-generation EGFR-TKIs and the presence of exon 19 deletions independently predicted longer PFS, while ECOG performance status > 1, the presence of compound mutations, and liver metastasis predicted shorter OS.ConclusionDespite our study failing to demonstrate superior efficacy or survival benefits of ICT combined with EGFR-TKIs compared to EGFR-TKI monotherapy, considering that international clinical guidelines recommend pleural drainage as a standard approach for managing MPE and the significant efficacy of third-generation EGFR-TKIs observed in our study for treating EGFR mutation-positive lung cancer patients with MPE, we speculate that the combination of third-generation EGFR-TKIs and pleural drainage may be a more rational treatment option for this patient population. Future studies are needed to further validate this hypothesis.